2018
DOI: 10.1515/reveh-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

The natural environment as a reservoir of pathogenic and non-pathogenic Acinetobacter species

Abstract: AbstractAcinetobacteris a genus of Gram-negative bacteria, which are oxidase-negative, exhibiting a twitching motility under a magnifying lens. Besides being important soil microorganisms, due to their contribution to the soil fertility,Acinetobacterspecies, particularlyA. baumannii, hold a prominent place within the genus because, it is the most virulent among the other species, causing varying de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 67 publications
0
26
0
1
Order By: Relevance
“…Acinetobacter baumannii ( A. baumannii ) has an inevitable ability to sustain harsh conditions and spread as a serious pathogen 1 4 . A. baumannii infects moist tissues such as mucous membranes or areas of the skin that are exposed to this pathogen, either through wound or injury 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii ( A. baumannii ) has an inevitable ability to sustain harsh conditions and spread as a serious pathogen 1 4 . A. baumannii infects moist tissues such as mucous membranes or areas of the skin that are exposed to this pathogen, either through wound or injury 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the samples from indoor and built environment, soil samples from parks, JUST university campus and roundabouts were collected to investigate the presence of A. baumannii in an attempt to have an insight into its possible reservoir. Soil supplies micro‐organisms with basic needs, making it one of the best environments for them to survive and thrive (Adewoyin & Okoh, 2018). Few studies have demonstrated the isolation of A. baumannii from soils, especially polluted and contaminated ones (Byrne‐Bailey et al, 2009; Furlan et al, 2018; Hafa et al, 2019; Hrenovic et al, 2014; Obuekwe et al, 2009; Ranjbariyan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae are a group of gram-negative bacteria with strong degradation ability for organic compounds, which dominate in many plant endophytic microflora and are the endophytic core microflora of many plant seeds; members of this family are related to plant health and/or disease ( Rossmann et al., 2012 ; Erlacher et al., 2015 ; Cernava et al., 2019 ; Zhang et al., 2020 ; Bziuk et al., 2021 ). In other relatively high-abundance core endo-bacteriome, Acinetobacter is a class of gram-negative bacteria, and some strains of this genus can grow hormones, solubilise phosphate, and produce siderophores, which can promote plant growth ( Sachdev et al., 2010 ; Rokhbakhsh-Zamin et al., 2011 ; Adewoyin and Okoh, 2018 ). In this study, Acinetobacter accounted for a relatively high proportion of Lhasa landraces and modern cultivars and was the most abundant bacterial genus in the seeds of modern cultivars.…”
Section: Discussionmentioning
confidence: 99%